The MAGIX focal plane time projection chamber. (April 2020) - Caiazza, S S; Achenbach, P; Aulenbacher, S; Biroth, M; Christmann, M; Denig, A; Doria, L; Geimer, J; Gülker, P; Littich, M; Lunkenheimer, S; Mauch, M; et al.
Abstract: The MAGIX experiment is a versatile system optimized for low-energy nuclear and particle physics measurements. The setup is currently under development and will be installed at the MESA electron accelerator, at the Institute for Nuclear Physics of the University of Mainz. The main detectors of that experiment are a couple of high-precision magnetic spectrometers, each of them equipped with a GEM-based TPC at the focal plane to achieve a momentum resolution and angular resolution at the scattering vertex respectively of ≈ δ P P < 10 − 4 a n d ≈ 1 1 mrad on scattered electron momenta between 1 MeV/c and 105 MeV/c. The limiting factor to achieve those results is the amount and uniformity of the material before the focal plane and even the presence of the TPC field cage can be relevant. Therefore we developed, and hereby introduce, an open field-cage TPC to fulfil those challenging requirements.